International journal of plasticity. (Oxford ; New York Pergamon, 1985)
The purpose of the journal is to report original research on all aspects of plastic deformation, damage and fracture behaviour of isotropic as well as anisotropic solids, including the thermodynamics of plasticity and fracture, continuum theory, and macroscopic as well as microscopic phenomena. The topics of interest include plastic behaviour of single crystals and polycrystalline metals, ceramics, rocks and soils, composites, nanocrystalline and microelectronics materials, shape memory alloys, ferroelectric ceramics, thin films and polymers, as well as plasticity aspects of failure and fracture mechanics. Significant experimental, numerical or theoretical contributions advancing the understanding of plastic behaviour of solids are of special interest, together with studies relating macroscopic to the microscopic behaviour of solids. Papers on modeling of finite nonlinear elastic deformation, with similarities to modeling of plastic deformation, are also welcome
Keywords: Plasticity -- Periodicals; Plasticity